A method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two paths
By separating the black tea residue into filtrate and filter residue, and combining it with materials such as polyvinyl alcohol and cellulose, liquid and solid plastic film materials are prepared, which solves the problem of difficult degradation of plastic film materials and achieves biodegradation and high-value utilization.
Patent Information
- Application Number
- CN202210513687.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-05-12
AI Technical Summary
The existing plastic film materials are difficult to degrade, resulting in environmental pollution and waste of resources. The poor dimensional stability of lignocellulose fibers in tea residues limits their application in membrane materials.
By pretreating the black tea residue, it is separated into two parts: filtrate and filter residue. The filtrate is blended with polyvinyl alcohol to prepare a liquid mulch. The filter residue is combined with cellulose and other materials, and solid mulch is prepared through phase conversion method and cross-linking treatment.
The prepared liquid and solid mulch materials have good biodegradability, sustainable regeneration and pollution-free characteristics. They can replace traditional mulch materials and improve soil fertility after degradation.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two dual paths, belonging to the field of chemical agricultural and forestry materials. Background Art
[0002] As one of the most widely used agricultural cultivation technologies in my country, mulching can increase crop yields, reduce pesticide inputs in farmland, save irrigation water, and help meet the growing demand for food, thus promoting the development of my country's agricultural economy. However, plastic mulch is difficult to degrade after being discarded, and the residual mulch has caused serious damage to the soil and ecological environment, and caused secondary pollution to the environment. Therefore, research on environmentally friendly biodegradable mulch has been carried out using agricultural and forestry waste as raw materials. Improving the production technology and methods of mulch, using non-toxic, environmentally friendly and degradable biomass raw materials, and developing and manufacturing excellent performance degradable liquid mulch and solid mulch are effective ways to solve the current film pollution problem.
[0003] Tea is considered the second largest beverage in the world after water. As one of the major tea producers, China produces a large amount of residual residues every year while producing tea polyphenols, tea beverages, instant tea and other products. The discarded tea residues still have a lot of nutrients. Directly discarding them will cause a huge waste of resources. Using tea residues as compost materials can have a positive impact on the soil. However, the lignocellulosic fibers contained in tea residues have poor dimensional stability and lack of thermoplasticity, which limits its application in membrane materials. Polyvinyl alcohol is a hydrolysis product of polyvinyl acetate and is very suitable for blending with natural polymer materials because it has high polarity, can be operated in aqueous solution, is biodegradable, and has good physical properties such as tensile strength and elongation at break. In addition, cellulose is one of the most commonly used natural substances and has become one of the most important commercial raw materials. It has low cost, high specific surface area, good biocompatibility and degradability. Therefore, tea residues can be modified and mixed with degradable materials such as polyvinyl alcohol and cellulose to make up for each other's shortcomings and thus be used in the preparation of ground film materials. Summary of the invention
[0004] The present invention provides a method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two parts and using two paths. The tea residue is divided into two parts, filtrate and residue, through a certain pretreatment process. The filtrate part is mixed with polyvinyl alcohol / polyethylene oxide solution in a certain proportion and then sprayed to obtain a liquid mulch; the residue part is evenly dispersed in a cellulose solution dissolved in a sodium hydroxide / urea system, and a cellulose / residue membrane is prepared by a phase inversion method. The membrane is then immersed in a sodium alginate / agar powder / glycerol mixed solution for modification and then transferred to a calcium chloride solution for cross-linking, and a solid mulch is obtained after drying.
[0005] To achieve the above-mentioned purpose, the liquid mulch prepared by the present invention has a thickness of 50~400μm, a tensile load strength of 1.5~10MPa in a dry state, an elongation at break of 60~310%, a tensile load strength of 0.5~8MPa in a wet state, and an elongation at break of 200~320%; the solid mulch has a thickness of 50~400μm, a tensile load strength of 8~80MPa in a dry state, an elongation at break of 0.5~10%, a tensile load strength of 0.5~20MPa in a wet state, and an elongation at break of 1~30%.
[0006] The technical solution adopted by the present invention is: a black tea residue is divided into two paths to prepare liquid mulch and solid mulch materials, firstly, a mixed solution of tea residue / sodium hydroxide / urea is prepared, and after low temperature, ultrasound and filtration, a filtrate and a residue are obtained. The filtrate part is blended with a polyvinyl alcohol / polyethylene oxide solution in a certain proportion and then sprayed to obtain a liquid mulch; the residue part is evenly dispersed in a cellulose solution dissolved in a sodium hydroxide / urea system, and a cellulose / residue membrane is prepared by a phase inversion method, and then the membrane is immersed in a sodium alginate / agar powder / glycerol mixed solution for modification and then transferred to a calcium chloride solution for cross-linking, and a solid mulch is obtained after drying.
[0007] The polyvinyl alcohol is a water-soluble polymer with a relative molecular weight of 20,000 to 150,000.
[0008] The polyethylene oxide is a water-soluble polymer with a relative molecular weight of 1 to 4 million.
[0009] The cellulose is natural cellulose extracted from one or more mixed pulps of cotton pulp, wood pulp, bamboo pulp or straw pulp.
[0010] The agar powder is a water-soluble plant gum with a relative molecular weight of 3000-8000.
[0011] The above-mentioned method of preparing liquid mulch and solid mulch materials by dividing black tea residue into two dual paths comprises the following steps:
[0012] (1) The tea residue is divided into two treatments: the tea residue is mixed with sodium hydroxide solution, stirred and heated, cooled to room temperature, and then urea is added for precooling, ultrasonication, and filtration to obtain filtrate and filter residue respectively. The mass percentage of each component of the tea residue / sodium hydroxide / urea mixed solution is 4-6% tea residue, 6-8% sodium hydroxide, 10-12% urea, and water is added. The heating temperature is 80-95°C, the precooling temperature is -20--10°C, and the ultrasonication time is 30-50 min;
[0013] (2) Preparation of liquid mulch: The filtrate from step (1) is mixed with a polyvinyl alcohol solution and a polyethylene oxide solution, and the pH of the solution is adjusted with citric acid before spraying to form a film. The mass percentage of each component of the mixed solution is 4-6% polyvinyl alcohol, 0.01-0.03% polyethylene oxide, 50% filtrate, and water to make up the rest;
[0014] (3) Preparation of solid mulch film: firstly, prepare a sodium hydroxide / urea system solution, precool it, add cellulose and the filter residue obtained in step (1) and evenly disperse them, and after ultrasonic degassing, use citric acid aqueous solution as a coagulation bath, and prepare a cellulose / filter residue membrane by phase inversion method. The mass percentage of each component of the casting solution is 6-8% sodium hydroxide, 10-12% urea, 2-4% cellulose, 1-3% filter residue, and water is used as the supplementary material. The precooling temperature is -20--10°C, and the concentration of citric acid aqueous solution is 0.6-0.8%. Then, the cellulose / filter residue membrane is immersed in a sodium alginate / agar powder / glycerol mixed solution for modification and then transferred to a calcium chloride solution for cross-linking. After drying, a solid mulch film is obtained. The mass percentage of each component of the sodium alginate / agar powder / glycerol mixed solution is 0.5-1.5% sodium alginate, 0.1-0.3% agar powder, 2-4% glycerol, and water is used as the supplementary material. The concentration of the calcium chloride solution is 3-5%.
[0015] The citric acid in step (2) and step (3) is one of anhydrous citric acid and monohydrate citric acid.
[0016] The beneficial effects of the present invention are: liquid mulch and solid mulch are prepared by taking tea residue as the main raw material and combining it with degradable materials such as polyvinyl alcohol and cellulose. The liquid mulch and solid mulch have the advantages of sustainable regeneration, no pollution, easy biodegradability, good biocompatibility, etc. After degradation, the soil fertility can be improved, and the high-value utilization of biomass materials such as tea residue and cellulose and the replacement of traditional mulch materials can be achieved. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit this example.
[0018] Example 1: Black tea residue is divided into two paths to prepare liquid mulch and solid mulch materials
[0019] (1) Tea residue is divided into two treatments: Mix the tea residue with sodium hydroxide solution, stir and heat, cool to room temperature, add urea for precooling, ultrasonicate, and filter to obtain filtrate and filter residue respectively. The mass percentage of each component of the tea residue / sodium hydroxide / urea mixed solution is 4% tea residue, 6% sodium hydroxide, 10% urea, and water is added. The heating temperature is 80°C, the precooling temperature is -20°C, and the ultrasonic time is 30 min.
[0020] (2) Preparation of liquid mulch: The filtrate from step (1) is mixed with a polyvinyl alcohol solution and a polyethylene oxide solution, and the pH of the solution is adjusted with citric acid before spraying to form a film. The mass percentage of each component of the mixed solution is 4% polyvinyl alcohol, 0.01% polyethylene oxide, 50% filtrate, and water as the balance;
[0021] (3) Preparation of solid mulch film: firstly, prepare a sodium hydroxide / urea system solution, precool it, add cellulose and the filter residue obtained in step (1) and evenly disperse them, and after ultrasonic degassing, use citric acid aqueous solution as a coagulation bath, and prepare a cellulose / filter residue membrane by phase inversion method. The mass percentage of each component of the casting solution is 6% sodium hydroxide, 10% urea, 2% cellulose, 1% filter residue, and water is used as the supplementary material. The precooling temperature is -20°C, and the concentration of citric acid aqueous solution is 0.6%. Then, the cellulose / filter residue membrane is immersed in a sodium alginate / agar powder / glycerol mixed solution for modification and then transferred to a calcium chloride solution for cross-linking. After drying, a solid mulch film is obtained. The mass percentage of each component of the sodium alginate / agar powder / glycerol mixed solution is 0.5% sodium alginate, 0.1% agar powder, 2% glycerol, and water is used as the supplementary material. The concentration of the calcium chloride solution is 3%.
[0022] Example 2: Black tea residue is divided into two paths to prepare liquid mulch and solid mulch materials
[0023] (1) Tea residue is divided into two treatments: Mix the tea residue with sodium hydroxide solution, stir and heat, cool to room temperature, add urea for precooling, ultrasonicate, and filter to obtain filtrate and filter residue respectively. The mass percentage of each component of the tea residue / sodium hydroxide / urea mixed solution is 5% tea residue, 7% sodium hydroxide, 11% urea, and water is added. The heating temperature is 85°C, the precooling temperature is -15°C, and the ultrasonic time is 40 min.
[0024] (2) Preparation of liquid mulch: The filtrate from step (1) is mixed with a polyvinyl alcohol solution and a polyethylene oxide solution, and the pH of the solution is adjusted with citric acid before spraying to form a film. The mass percentage of each component of the mixed solution is 5% polyvinyl alcohol, 0.02% polyethylene oxide, 50% filtrate, and the balance is water;
[0025] (3) Preparation of solid mulch film: firstly, prepare a sodium hydroxide / urea system solution, precool it, add cellulose and the filter residue obtained in step (1) and evenly disperse them, and after ultrasonic degassing, use citric acid aqueous solution as a coagulation bath, and prepare a cellulose / filter residue membrane by phase inversion method. The mass percentage of each component of the casting solution is 7% sodium hydroxide, 11% urea, 3% cellulose, 2% filter residue, and water is used as the supplementary material. The precooling temperature is -15°C, and the concentration of citric acid aqueous solution is 0.7%. Then, the cellulose / filter residue membrane is immersed in a sodium alginate / agar powder / glycerol mixed solution for modification and then transferred to a calcium chloride solution for cross-linking. After drying, a solid mulch film is obtained. The mass percentage of each component of the sodium alginate / agar powder / glycerol mixed solution is 1% sodium alginate, 0.2% agar powder, 3% glycerol, and water is used as the supplementary material. The concentration of the calcium chloride solution is 4%.
[0026] Example 3: Black tea residue is divided into two paths to prepare liquid mulch and solid mulch materials
[0027] (1) Tea residue is divided into two treatments: Mix the tea residue with sodium hydroxide solution, stir and heat, cool to room temperature, add urea for precooling, ultrasonicate, and filter to obtain filtrate and filter residue respectively. The mass percentage of each component of the tea residue / sodium hydroxide / urea mixed solution is 6% tea residue, 8% sodium hydroxide, 12% urea, and water is added. The heating temperature is 95°C, the precooling temperature is -10°C, and the ultrasonic time is 50 min.
[0028] (2) Preparation of liquid mulch: The filtrate from step (1) is mixed with a polyvinyl alcohol solution and a polyethylene oxide solution, and the pH of the solution is adjusted with citric acid before spraying to form a film. The mass percentage of each component of the mixed solution is 6% polyvinyl alcohol, 0.03% polyethylene oxide, 50% filtrate, and the balance is water;
[0029] (3) Preparation of solid mulch film: firstly, prepare a sodium hydroxide / urea system solution, precool it, add cellulose and the filter residue obtained in step (1) and evenly disperse them, and after ultrasonic degassing, use citric acid aqueous solution as a coagulation bath, and prepare a cellulose / filter residue membrane by phase inversion method. The mass percentage of each component of the casting solution is 8% sodium hydroxide, 12% urea, 4% cellulose, 3% filter residue, and water is used as the supplementary material. The precooling temperature is -10°C, and the concentration of citric acid aqueous solution is 0.8%. Then, the cellulose / filter residue membrane is immersed in a sodium alginate / agar powder / glycerol mixed solution for modification and then transferred to a calcium chloride solution for cross-linking. After drying, a solid mulch film is obtained. The mass percentage of each component of the sodium alginate / agar powder / glycerol mixed solution is 1.5% sodium alginate, 0.3% agar powder, 4% glycerol, and water is used as the supplementary material. The concentration of the calcium chloride solution is 5%.
[0030] The liquid mulch and solid mulch materials produced in Examples 1-3 were tested: the thickness of the liquid mulch was 50~400μm, the tensile load strength in a dry state was 5~10MPa, and the elongation at break was 180~310%; the tensile load strength in a wet state was 3.5~8MPa, and the elongation at break was 250~320%; the thickness of the solid mulch was 50~400μm, the tensile load strength in a dry state was 20~60MPa, and the elongation at break was 1~8%; the tensile load strength in a wet state was 1~15MPa, and the elongation at break was 5~20%.
[0031] The above description points out and describes several preferred embodiments of the present invention, but it should be understood that the present invention is not limited to the form disclosed herein and should not be regarded as excluding other embodiments. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two dual paths, characterized in that: Firstly, a mixed solution of tea residue / sodium hydroxide / urea is prepared, and after low temperature, ultrasound and filtration, a filtrate and a residue are obtained; the filtrate is mixed with a polyvinyl alcohol / polyethylene oxide solution in a certain proportion and then sprayed to obtain a liquid mulch film; the residue is evenly dispersed in a cellulose solution dissolved in a sodium hydroxide / urea system, and a cellulose / residue membrane is prepared by a phase inversion method; the membrane is then immersed in a mixed solution of sodium alginate / agar powder / glycerol for modification and then transferred to a calcium chloride solution for cross-linking, and a solid mulch film is obtained after drying.
2. The method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two paths according to claim 1, characterized in that: The thickness of the liquid mulch film is 50 to 400 μm, the tensile load strength in a dry state is 1.5 to 10 MPa, the elongation at break is 60 to 310%, the tensile load strength in a wet state is 0.5 to 8 MPa, and the elongation at break is 200 to 320%; the thickness of the solid mulch film is 50 to 400 μm, the tensile load strength in a dry state is 8 to 80 MPa, the elongation at break is 0.5 to 10%, the tensile load strength in a wet state is 0.5 to 20 MPa, and the elongation at break is 1 to 30%.
3. The method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two paths according to claim 1, characterized in that: The polyvinyl alcohol is a water-soluble polymer with a relative molecular weight of 20,000 to 150,000.
4. The method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two paths according to claim 1, characterized in that: The polyethylene oxide is a water-soluble polymer with a relative molecular weight of 1 to 4 million.
5. The method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two paths according to claim 1, characterized in that: The cellulose is natural cellulose extracted from one or more mixed pulps of cotton pulp, wood pulp, bamboo pulp or straw pulp.
6. The method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two paths according to claim 1, characterized in that: The agar powder is a water-soluble plant gum with a relative molecular weight of 3000-8000.
7. A method for preparing liquid mulch and solid mulch materials by dividing the black tea residue into two dual paths as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Tea residue is divided into two treatments: tea residue is mixed with sodium hydroxide solution, stirred and heated, cooled to room temperature, and then urea is added for precooling, ultrasonication, and filtration to obtain filtrate and filter residue respectively; the mass percentage of each component of the tea residue / sodium hydroxide / urea mixed solution is 4-6% of tea residue, 6-8% of sodium hydroxide, 10-12% of urea, and water is added; the heating temperature is 80-95°C, the precooling temperature is -20--10°C, and the ultrasonication time is 30-50min; (2) Preparation of liquid mulch: the filtrate of step (1) is mixed with a polyvinyl alcohol solution and a polyethylene oxide solution, and the pH of the solution is adjusted with citric acid before spraying to form a film; the mass percentage of each component of the mixed solution is 4-6% polyvinyl alcohol, 0.01-0.03% polyethylene oxide, 50% filtrate, and water as the balance; (3) Preparation of solid mulch film: firstly, prepare a sodium hydroxide / urea system solution, precool it, add cellulose and the filter residue obtained in step (1) and evenly disperse them, and after ultrasonic degassing, use citric acid aqueous solution as a coagulation bath, and prepare a cellulose / filter residue membrane by phase inversion method, the mass percentage of each component of the casting solution is 6-8% sodium hydroxide, 10-12% urea, 2-4% cellulose, 1-3% filter residue, and water is added, the precooling temperature is -20 to -10°C, and the concentration of citric acid aqueous solution is 0.6 to 0.8%; then, the cellulose / filter residue membrane is immersed in a sodium alginate / agar powder / glycerol mixed solution for modification and then transferred to a calcium chloride solution for cross-linking, and dried to obtain a solid mulch film, the mass percentage of each component of the sodium alginate / agar powder / glycerol mixed solution is 0.5-1.5% sodium alginate, 0.1-0.3% agar powder, 2-4% glycerol, and water is added, and the concentration of the calcium chloride solution is 3-5%.
8. The method for preparing liquid mulch and solid mulch materials by dividing black tea residue into two paths according to claim 7, characterized in that: The citric acid in step (2) and step (3) is one of anhydrous citric acid and monohydrate citric acid.
Citation Information
Patent Citations
Biodegradable plastic taking tea leaf residues as raw material and preparation method of biodegradable plastic
CN104744958A
Polyvinyl alcohol / polyoxyethylene synergistic enhanced chitin material and production method and purpose thereof
CN107163306A